Effect of Daily Lactococcus cremoris spp. Consumption Immobilized on Oat Flakes on Blood and Urine Biomarkers: A Randomized Placebo-Controlled Clinical Trial - Panoraia Bousdouni; Aikaterini Kandyliari; Anastasia Kargadouri; Panagiota Potsaki; Olga I. Papagianni; Maria-Eleni Stylianou; Nikoletta Stathopoulou; Panagiota Andrianopoulou; Maria Kapsokefalou; Vasiliki Bountziouka; Anastasia Kolomvotsou; Ioanna Prapa; et al. (Medicina)
Background and Objectives: The development of non-dairy probiotic products is a challenge for the food industry, while cereals, as probiotic carriers, provide the means to incorporate probiotics, prebiotics, and fiber into the human diet. The present study investigated the effects of Lactococcus cremoris spp. immobilized on oat flakes on blood and urine biomarkers in a randomized placebo-controlled single-blind clinical trial. Materials and Methods: Fifty-four eligible participants were randomized into a placebo or probiotic group that consumed 5 g of oat flakes daily for 12 weeks. Blood and urine samples were collected at the baseline, 6 weeks, and 12 weeks to assess the glycemic, lipemic, inflammatory, immunological, and antioxidant biomarkers, as well as the vitamin levels. Results: The intervention group exhibited a significant reduction in their hs-CRP levels (p = 0.002) and a trend toward decreased IL-6 levels (p = 0.035) at week 12 compared to the control group, suggesting a potential anti-inflammatory effect. Additionally, a significant reduction in insulin levels was observed in the probiotic group at week 6, with a clinical trend toward differentiation despite the absence of statistically significant differences between the groups. Furthermore, there were promising results regarding certain biomarkers, such as vitamin B12 and cortisol levels, in the probiotic group. Conclusions: The twelve-week consumption of Lactococcus cremoris spp. immobilized on oat flakes resulted in improvements in inflammatory, metabolic, and stress-related biomarkers. These results support the examined concept of non-dairy probiotic products, though further research is needed to confirm their efficacy and clarify their underlying mechanisms.